Thrombopoietin-receptor agonists for adult patients with immune thrombocytopenia: a narrative review and an approach for managing patients fasting intermittently - Yassin, Mohamed A.; Al-Rasheed, Mona; Al-Khaboori, Murtadha; Marashi, Mahmoud; Osman, Hani; Wali, Yasser; Al Kindi, Salam; Alsayegh, Faisal; Provan, Drew (Frontiers in Cardiovascular Medicine, 2023)
Introduction Thrombopoietin-receptor agonist (TPO-RAs) currently represent the state of art for treating immune thrombocytopenia. Their different molecular structures contribute to the difference in their pharmacodynamics and pharmacokinetics. This narrative review aims to provide an overview of the current TPO-RAs approved for primary immune thrombocytopenia (romiplostim, eltrombopag, avatrombopag) and the effect of intermittent fasting in adult patients receiving TPO-RAs. Areas covered Literature was searched with no limits on date or language, using various combinations of keywords. Data on the pharmacokinetics, pharmacodynamics, efficacy, and safety of TPO-RAs and the effect of intermittent fasting were summarized. Expert opinion Switching between TPO-RAs is a useful strategy to tackle some associated limitations. Romiplostim and avatrombopag have an advantage over eltrombopag as they do not require any dietary restrictions. In cases where romiplostim and avatrombopag are unavailable, patients should be educated on the appropriate administration, possible interactions, and dietary restrictions before initiating eltrombopag.